A tolerogenic peptide that induces suppressor of cytokine signaling (SOCS)-1 restores the aberrant control of IFN-gamma signaling in lupus-affected (NZB x NZW)F1 mice - Sharabi, Amir (Clinical immunology (Orlando, Fla.), 2009)
Interferon-gamma (IFN-gamma) plays a pathogenic role in systemic lupus erythematosus (SLE). Uncontrolled IFN-gamma signaling may result from a deficiency in the negative regulator, namely, suppressor of cytokine signaling-1 (SOCS-1). We investigated the activation status of IFN-gamma signaling pathway in SLE-afflicted (New-Zealand-BlackxNew-Zealand-White)F1 mice and determined its responsiveness when treating with a tolerogenic peptide, hCDR1, which ameliorates SLE. SOCS-1 was suppressed and pSTAT1 was enhanced in spleen-derived cells from SLE-affected mice as compared with healthy controls. Treatment with hCDR1 reversed the expression of these two molecules in association with clinical amelioration. In vitro stimulation with IFN-gamma resulted in elevated levels of SOCS-1 in cells from both vehicle and hCDR1-treated mice but this effect reached significance only in cells of the latter group, which also exhibited reduced levels of pSTAT1. Thus, SOCS-1 is diminished in SLE-affected mice, and treatment with hCDR1 results in its up-regulation thereby restoring control of IFN-gamma signaling pathway